A model to develop effective virtual teams - Lin, Chad; Standing, C.; Liu, Y. (Elsevier Publications, 2008)
A reviewof the literature shows the factors that impact on the effectiveness of virtual teams arestill ambiguous. To address this problem we developed a research design that included a metaanalysisof the literature, a field experiment and survey. The meta-analysis identified factorswhich impact on the effectiveness of virtual teams which were then validated by a fieldexperiment and survey. The results of the study indicate that social dimensional factors need tobe considered early on in the virtual team creation process and are critical to the effectivenessof the team. Communication is a tool that directly influences the social dimensions of the teamand in addition the performance of the team has a positive impact on satisfaction with thevirtual team. A major contribution of the paper is an integrated model of factors that contributeto virtual team effectiveness.